Efficacy and Safety of Ceftiofur for Treating Serious Respiratory Diseases in Cattle: Clinical, Histopathological, and Microbiological Assessments - Al-Awseya, Rasha A.H.; Hassan, Mostafa F.; Abdel Fatah, Abdel Fatah M.; Khalil, Waleed F.; Basha, Walaa A.A.; El-Tarabili, Reham M.; Hanna, Pierre A.; Gabr, Elsayed M. (Journal of Advanced Veterinary Research, 2023)
Bovine respiratory disease (BRD) is one of the most serious diseases counted for economic loss and extensive usage of antibiotics in cattle. Ceftiofur, a third-generation cephalosporin antibiotic, has been approved for use in cattle in the United States. This study was done to investigate the clinical effect of ceftiofur on calves as well as its efficacy and safety for treating BRD. Thirty Holstein calves from a dairy farm were divided into three groups. Group I served as a health control group. Group II consisted of healthy animals while Group III comprised calves clinically diagnosed with BRD. Both groups II and III received a single subcutaneous injection of ceftiofur (2mg/kg B.W) in the ear. All groups were clinically evaluated at day 0, 7, and 14 after drug administration for illness score, body weight, body gain, feed intake, body temperature, depression score, discharges, ear and coughing score. Clinical illness score showed clear signs of BRD (elevation of body temperature and depression). Nasal and ocular discharges were recorded and ranked. Significant increases in ear and coughing score were observed in diseased calves.